Civic Integrative Teacher Competence (CITeC): Mapping Competencies to Strengthen Elementary Students’ Digital Citizenship - Hamidaturrohmah Hamidaturrohmah; Muh. Muhaimin (Universitas Muhammadiyah Mataram, 2026)
Abstract: Strengthening elementary students’ civic character in the digital era is a major challenge in Pancasila education or PKn. This study maps teacher competencies that support the development of students’ civic knowledge, attitudes, and skills through classroom instructional practices. A Systematic Literature Review (SLR) was conducted on 25 national and international articles published from 2019 to 2026 using a structured literature synthesis matrix as the data analysis instrument. Thematic analysis was used to identify patterns and classify teacher competencies. Findings show that the five core teacher competencies pedagogical, professional, social, personal, and digital have evolved into seven key competencies: civic pedagogic, contextual professional, socio-personal, 21st-century skills, digital pedagogic, democratic socio-emotional, and collaborative civic ecosystem. These competencies are integrated into the Civic Integrative Teacher Competence (CITeC) framework, which emphasizes that strengthening students’ civic character occurs through contextual learning, a democratic classroom climate, positive social interaction, and ethical technology use. The CITeC framework provides a basis for designing participatory and reflective strategies, models, and approaches in Pancasila education that are relevant to students’ needs in the digital era.Abstrak: Penguatan karakter kewargaan murid sekolah dasar di era digital menjadi tantangan utama dalam pembelajaran Pendidikan Pancasila atau PKn. Penelitian ini memetakan kompetensi guru yang mendukung pengembangan pengetahuan, sikap, dan keterampilan kewargaan murid melalui praktik pembelajaran di kelas. Metode penelitian menggunakan Systematic Literature Review (SLR) terhadap 25 artikel nasional dan internasional yang diterbitkan antara 2019–2026 dengan bantuan matriks sintesis literatur sebagai perangkat analisis data. Analisis tematik diterapkan untuk mengidentifikasi pola dan mengklasifikasikan kompetensi guru. Hasil penelitian menunjukkan bahwa lima kompetensi inti guru pedagogik, profesional, sosial, kepribadian, dan digital berevolusi menjadi tujuh kompetensi utama: pedagogis kewargaan, profesional kontekstual, sosial-kepribadian, keterampilan abad ke-21, pedagogis digital, sosial-emosional demokratis, dan kolaboratif ekosistem kewargaan. Ketujuh kompetensi ini terintegrasi dalam kerangka Civic Integrative Teacher Competence (CITeC), yang menekankan bahwa penguatan karakter kewargaan murid berlangsung melalui pembelajaran kontekstual, iklim kelas demokratis, interaksi sosial positif, dan pemanfaatan teknologi secara etis. Kerangka CITeC menjadi dasar perancangan strategi, model, dan pendekatan pembelajaran Pancasila yang partisipatif, reflektif, dan relevan dengan kebutuhan murid di era digital.